CONCEPT OF ASSESSMENT OF THE ECONOMIC DEVELOPMENT POTENTIAL OF SMALL BUSINESS AND ITS EVALUATION - Israilov, Rusrambek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Small businesses are a vital part of any economy, providing jobs, income, and goods and services to communities around the world. “According to the Small Business Administration (SBA), there are more than 31 million small businesses in the United States alone, employing nearly 60 million people. [1] However, despite their importance, many small businesses fail in their first few years of operation. Small businesses play a crucial role in the economy of any country. They are the backbone of the economy, contributing to job creation, economic growth, and social development. Small businesses create jobs and provide employment to millions of people around the world. “In most countries, small businesses account for a significant portion of total employment. According to the World Bank, small and medium-sized enterprises (SMEs) account for more than 90% of businesses worldwide and contribute to more than 50% of total employment.” [2]